Human health risk assessment of aluminium in water treated with aluminium-based coagulants in a rural area - Fernando García-Ávila; Tatiana Encalada-Alvear; Luis M. Alvarez-Altamirano; Alex Avilés-Añazco; Lorgio Valdiviezo-Gonzalez; Emigdio Alfaro-Paredes (Results in Engineering)
The use of aluminium salts as coagulants in drinking water treatment raises questions about potential public health risks, due to high levels of residual aluminium in water supplies. This study assessed the non-carcinogenic risk associated with aluminium in drinking water supplied by the water treatment plant in Aurelio Bayas district, Ecuador, a rural region facing significant challenges for accessing safe drinking water, mainly due to the absence of regular water quality monitoring. Monthly samples were collected and analyzed at 20 points in the drinking water distribution network during three summer and three winter months, assessing residual aluminium and other physicochemical parameters. The risk assessment was carried out using the Hazard Index (HI), which allows the quantification of the potential risk associated with exposure to aluminium through drinking water. This approach is based on the comparison of the aluminium concentrations found with the reference doses established by public health agencies. The results revealed significant variations in the concentration of aluminium between seasons, although all measurements remained within the limits allowed by Ecuadorian regulations and the WHO, which sets a limit of 0.2 mg/L for aluminium in drinking water. The average residual aluminium concentrations were 0.028 mg/L in the dry season and 0.019 mg/L in the wet season. The calculated HI for children and adults showed no health risks with values below 1, although it was higher in children than in adults during both seasons. The presence of aluminium in drinking water does not represent a danger to the health of consumers.